A Brief Analysis of Refugees and Crime Issues on the Myanmar-Thailand Border Based on the Focus-Field Methodology - Yang, Jiaolian (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
The border region between Myanmar and Thailand, as a complex area where historical legacies and contemporary circumstances intersect, has garnered significant attention from regional countries. The focus-field methodology, a research approach in regional and country studies characterized by its “six major attributes,” provides a verifiable, effective, and appropriate framework for in-depth analysis and understanding of the issues arising in this region. By tracing the colonial historical roots of the refugee crisis and the current policy imbalances, decoding the underlying causes of criminal disorder, revealing the interactive dynamics within the “power vacuum zone,” precisely analyzing the activities of various stakeholders, and identifying universally prevalent “common” challenges, it becomes clear that a comprehensive solution is required. To break the deadlock, a “dual-track” governance framework must be established: Myanmar and Thailand need to urgently develop a collaborative border law enforcement and livelihood security system, while the international community should create a long-term intervention mechanism through financial assistance, intelligence sharing, and judicial cooperation, offering a pathway to address all “similar problems.”